Case 3702: Verconella dilatata var. cuvieriana Powell, 1927 (currently Penion cuvierianus; Mollusca, Gastropoda, Buccinoidea): proposed conservation of the specific name - Marshall, Bruce A; Beu, Alan G; Ponder, Winston F; Spencer, Hamish G; Walton, Kerry; Willan, Richard C (Bulletin of Zoological Nomenclature, 2016)
See BZN 75 (2018): 85.